Lease on love : a novel - Ballard, Falon (G. P. Putnam's Sons, 2022)
"Beach Read meets The Flatshare in this warmly funny and delightfully sharp debut rom-com about a down-on-her-luck young woman who turns an innocent mix-up between a dating app and a roommate app into a new chance at love"--